Hashimoto’s Encephalopathy Mimicking Viral Encephalitis: A Case Report - Yu, Miaomiao; Yang, Yu; Ma, Xianyi; Xie, Yinyin; Sun, Ningning; Meng, Hongmei (Frontiers in Neuroscience, 2020)
Hashimoto’s encephalopathy (HE) is a rare neuropsychiatric syndrome characterized by elevated levels of anti-thyroid antibodies. Manifestations of HE are diverse, making it difficult to diagnose in a timely manner. Herein, we report a case of HE, in which the clinical symptoms and laboratory test results mimicked viral encephalitis. The patient, who presented with a fever, headache, awkward speech, sentence confusion, elevated levels of anti-thyroid antibodies in the serum, an increased white blood cell count, and positive anti-thyroid antibodies in the CSF, was finally diagnosed with HE and responded well to a small dose of methylprednisolone. With this report, we aim to increase the awareness of HE, and remind clinicians to take HE into consideration when facing cases of unexplained encephalopathy.